Adsorption removal of Congo red onto L-cysteine/rGO/PANI nanocomposite: equilibrium, kinetics and thermodynamic studies. Issue 1 (1st January 2021) - Razzaq, Saba; Akhtar, Mehwish; Zulfiqar, Sonia; Zafar, Shagufta; Shakir, Imran; Agboola, Philips O.; Haider, Sajjad; Warsi, Muhammad Farooq
Abstract : In this paper, adsorption of Congo red (CR) onto L-cysteine decorated with reduced graphene oxide/polyaniline composite at room temperature was investigated. The morphology and structure properties of as-prepared nanocomposite were verified by UV–visible spectroscopy (UV–visible), powder X-ray diffraction (XRD), Fourier transform infrared spectrophotometry (FTIR), scanning electron microscopy (SEM), and Brunauer Emmett Teller (BET) studies. Effect ofabsorbent dosage, contact time, initial dye concentration and temperature were studied and optimal conditions for the adsorption process of Congo red dye were found. The obtained results indicated that isotherms data fitted well to Langmuir model. While kinetics data fitted well to the pseudo-second-order kinetic equation and the adsorption process was generally governed via intra-particle diffusion. Thermodynamic data showed that adsorption process of CR was endothermic and spontaneous in nature. At optimal conditions, the maximum adsorption capacity of CR was calculated and found to be 56.57 mg/g, which shows that L-cysteine functionalized reduced graphene oxide/polyaniline based nanocomposite can be efficiently used for wastewater management.